Comparison of Laboratory Methods for Analysis of Non-nucleoside Reverse Transcriptase Inhibitor Resistance in Ugandan Infants - Church, Jessica D.; Huang, Wei; Parkin, Neil; Marlowe, Natalia; Guay, Laura A.; Omer, Saad B.; Musoke, Philippa; Jackson, J. Brooks; Eshleman, Susan H. (My University, 2009)
Detailed comparisons of HIV drug resistance assays are needed to identify the most useful assays for research studies, and to facilitate comparison of results from studies that use different methods. We analyzed nonnucleoside reverse transcriptase inhibitor (NNRTI) resistance in 40 HIV-infected Ugandan infants who had received nevirapine (NVP)-based prophylaxis using the following assays: an FDA-cleared HIV genotyping assay (the ViroSeq HIV-1 Genotyping System v2.0), a commercially available HIV genotyping assay (GeneSeq HIV), a commercially available HIV phenotyping assay (PhenoSense HIV), and a sensitive point mutation assay (LigAmp). ViroSeq and GeneSeq HIV results (NVP resistance yes=no) were similar for 38 (95%) of 40 samples. In 6 (15%) of 40 samples, GeneSeq HIV detected mutations in minor subpopulations that were not detected by ViroSeq, which identified two additional infants with NVP resistance. LigAmp detected low-level mutations in 12 samples that were not detected by ViroSeq; however, LigAmp testing identified only one additional infant with NVP resistance. GeneSeq HIV and PhenoSense HIV determinations of susceptibility differed for specific NNRTIs in 12 (31%) of the 39 samples containing mixtures at relevant mutation positions. PhenoSense HIV did not detect any infants with NVP resistance who were not identified with GeneSeq HIV testing. In this setting, population sequencing-based methods (ViroSeq and GeneSeq HIV) were the most informative and had concordant results for 95% of the samples. LigAmp was useful for the detection and quantification of minority variants. PhenoSense HIV provided a direct and quantitative measure of NNRTI susceptibility.
Keywords: Laboratory Methods; Analysis; Non-nucleoside; Reverse; Transcriptase; Resistance; Ugandan Infants